TREATMENT OF STABILE ISCHEMIC HEART DISEASE: IS CORONARY STENTING SUPERIOR OVER DRUG THERAPY? - Sergei G. Kanorskii; Natal’ya V. Smolenskaya (Кубанский научный медицинский вестник, 2019)
The results of the most discussed randomized trials of percutaneous coronary intervention (PCI) in comparison with drug therapy (COURAGE and FAME 2) and PCI imitation (ORBITA) in patients with stable coronary heart disease are analyzed. Information on the ongoing ISCHEMIA trial is presented. Different points of view are compared concerning the results of the most important PCI research projects. Factors that can distort the results and the possibilities of their elimination are discussed. The main provisions of the American (2017) and European (2018) Guidelines on myocardial revascularization with a focus on PCI in patients with stable coronary heart disease are described.Conflict of interest: the authors declare no conflict of interest.